2019
DOI: 10.3390/agriculture9050107
|View full text |Cite
|
Sign up to set email alerts
|

A First Description of the Phenolic Profile of EVOOs from the Maltese Islands Using SPE and HPLC: Pedo-Climatic Conditions Modulate Genetic Factors

Abstract: Achieving economic sustainability in the olive oil production sector is a challenge. This is particularly so for small scale producers who are faced with pressing, production and marketing costs that relative to overall sales, minimise profits. In this study we aimed to describe the phenolic profile of extra virgin olive oils (EVOOs) derived from the Maltese islands. The polar fractions from EVOOs from nine indigenous (six Bidni and three Malti), one historically acclimatized tree (Bajda), 12 locally-grown but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Whilst the 'Bidni' and 'Bajda' are monocultivars, the 'Malti' is thought to be made up of several ancient varieties which are geographically isolated from each other [22]. Furthermore, recent studies have shown that Maltese EVOOs have a significantly different phenolic composition and mineral composition [23,24]. In this study, a variety of olive oils selected from different areas around the Maltese islands and countries around the Mediterranean were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the 'Bidni' and 'Bajda' are monocultivars, the 'Malti' is thought to be made up of several ancient varieties which are geographically isolated from each other [22]. Furthermore, recent studies have shown that Maltese EVOOs have a significantly different phenolic composition and mineral composition [23,24]. In this study, a variety of olive oils selected from different areas around the Maltese islands and countries around the Mediterranean were studied.…”
Section: Introductionmentioning
confidence: 99%
“…The high content of MUFA, particularly the oleic acid, and phenolic compounds can protect the oil to oxidation [ 35 ]. Similar ivory-white cultivars (Leucocarpa and Bajda) had been previously studied without reporting the fatty acid profile [ 13 , 14 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, there is little information on the phenolic profile of virgin olive of ivory-white olives. In a previous study carried out with Bajda cultivar, oleacein, oleocanthal, oleuropein aglycone, and ligstroside aglycone were only identified but not quantified [ 16 ]. Leucocarpa cultivar also was analyzed and low concentrations of oleuropein aglycone were detected in the fruit (6.63 ± 0.22 to 16.8 ± 0.07 mg/g of fresh weight) whereas other compounds were not analyzed [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations